Rupture of the normal aortic valve after blunt chest trauma. Issue 5 (October 1977) - Chi, S; Blair, T C; Gonzalez-Lavin, L
Abstract : Rupture of the normal aortic valve after blunt trauma to the chest is seen infrequently. With the ever-increasing incidence of car and motorcycle accidents, this injury should be considered during the initial examination of an accident victim. Any patient without a history of heart disease presenting with heart murmurs after severe blunt trauma to the chest should give rise to the suspicion of aortic valve damage. When the diagnosis is proved, aortic valve expoloration is necessary. Review of the published cases establishes that valve replacement is the treatment of choice.